Dynamic identities and the construction of transcultural architectures - Hernandez, Felipe M. (2002)
Latin American architectural theory has not been successful in dealing with the complexity of Latin American cultures, and in engaging with the whole range of architectural practices that take place in the continent's cities and buildings. On the contrary, in most cases, architectural theories have been used as means to create hegemonic architectural narratives and systems of referentiality through which a sense of homogeneity could be reconstituted. Consequently, architectural theory appears to be in radical opposition to the realities of Latin American cultures and societies. This thesis does therefore engage in detail with cultural theory and postcolonial discourse, and uses post-structuralist methods of critique, as a means to engage with the whole range of politics and socio-cultural practices with which architecture is inherently related. Approached via the work of various cultural theorists, the complex reality of Latin America is not seen as a problem that requires resolution through the elimination of differences. On the contrary, and unlike architects and architectural theorists, cultural theorists aim their efforts at revealing those areas of conflict where the very fractures of Latin American cultures can be found, and where diverse and often antagonistic socio-cultural groups clash while attempting to negotiate their differences. Only in this way would it be possible to create a cultural politics of difference in order to deal with cultural multiplicity in situations of inequality. Engagement with broader aspects of cultural theory will provide the possibility of questioning the validity and sufficiency of existing methods of architectural analysis in Latin America. That is why the most prominent theoretical models that have been created in Latin America during the past twenty- five years will here be placed under scrutiny. Greater engagement with issues outside an exclusively architectural discourse will not only bring to light the shortcomings of existing methods of analysis, but also provide the means to correct and enhance them. In this way, aspects that have been little theorized or which have remained invisible to the eyes of architects and architectural theorists will be revealed. The theories examined throughout this thesis will also provide the means to validate minority architectural practices that have so far been dismissed for not corresponding to parameters established by hegemonic architectural narratives.